In vivo evidence suggesting reciprocal renal hypoxia-inducible factor-1 upregulation and signal transducer and activator of transcription 3 activation in response to hypoxic and non-hypoxic stimuli - Nechemia-Arbely, Yael; Khamaisi, Mogher; Rosenberger, Christian; Koesters, Robert; Shina, Ahuva; Geva, Carmit; Shriki, Anat; Klaus, Stephen; Rosen, Seymour; Rose-John, Stefan; Galun, Eithan; Axelrod, Jonathan H; et al. (Clinical and experimental pharmacology and physiology, 2013)
In vitro studies suggest that combined activation of hypoxia-inducible factor (HIF) and signal transducer and activator of transcription 3 (STAT3) promotes the hypoxia response. However, their interrelationship in vivo remains poorly defined. The present study investigated the possible relationship between HIF-1 upregulation and STAT3 activation in the rodent kidney in vivo. Activation of HIF-1 and STAT3 was analysed by immunohistochemical staining and western blot analysis in: (i) models of hypoxia-associated kidney injury induced by radiocontrast media or rhabdomyolysis; (ii) following activation of STAT3 by the interleukin (IL)-6-soluble IL-6 receptor complex; or (iii) following HIF-1α stabilization using hypoxic and non-hypoxic stimuli (mimosine, FG-4497, CO, CoCl2) and in targeted von Hippel-Lindau-knockout mice. Western blot analysis and immunostaining revealed marked induction of both transcription factors under all conditions tested, suggesting that in vivo STAT3 can trigger HIF and vice versa. Colocalization of HIF-1α and phosphorylated STAT3 was detected in some, but not all, renal cell types, suggesting that in some cells a paracrine mechanism may be responsible for the reciprocal activation of the two transcription factors. Nevertheless, in several cell types spatial concordance was observed under the majority of conditions tested, suggesting that HIF-1 and STAT3 may act as cotranscription factors. These in vivo studies suggest that, in response to renal hypoxic-stress, upregulation of HIF-1 and activation of STAT3 may be both reciprocal and cell type dependent.
Gesehen am 08.12.2021